Lead by example? The dissemination of ethical values through authentic leader inspiration. Issue 4 (31st October 2019) - Hattke, Fabian; Hattke, Judith
Abstract : Purpose: The purpose of this paper is to propose that leaders who promote ethical values authentically will be more effective in inspiring followers to behave ethically than inauthentic leaders. It further hypothesizes that authentic ethical inspiration by leaders will transform followers' prosocial motivation so that they internalize their leader's values and act accordingly. Design/methodology/approach: The study tests this moderated-mediation model based on survey data from 741 officers in the Federal Armed Forces Germany who are leaders and follower simultaneously. Findings: Leader authenticity moderates the relationship between leader ethical influence and follower ethical behaviors. The effect is significant and substantial. Leader ethical influence has a significant, yet marginal effect on follower prosocial motivation, which, in turn, strongly relates to follower ethical behaviors. Research limitations/implications: Although leader authenticity is a value in itself, it says little about the contents of leaders' ethical values. Thus, future research should not confound authentic leadership with ethical leadership. Prosocial motivation is a comparatively stable characteristic of individuals, which is rather resilient against leader influence. Practical implications: "Softer" means of leader influence are effective in the coercive context of public command-and-control organizations. By cascading down the hierarchy, ethical values disseminate throughout the organization. The study draws these conclusions within the limitations of a cross-sectional analysis. Originality/value: This study is the first to investigate the moderating role of perceived leader authenticity in the relationship between leader ethical inspiration and follower ethical behaviors.